TIRAP (MAL) S180L polymorphism is a common protective factor against developing tuberculosis and systemic lupus erythematosus (2008)
Background and aim: The involvement of Toll-like receptor (TLR)-mediated pathways in infectious and autoimmunity has been suggested. The MyD88 adaptor-like (Mal) protein, also known as the TIR domain-containing adaptor protein (TIRAP), is implicated in the TLR2- and TLR4-mediated MyD88-dependent signaling pathway. The aim of this study was to investigate the influence of the functional TIRAP (MAL) S180L polymorphism on tuberculosis (TB) and four autoimmune diseases namely: rheumatoid arthritis (RA), primary Sjögren's syndrome (pSS), systemic lupus erythematosus (SLE) and type 1 diabetes mellitus (T1D). Methods: This was a case-control and family based association study in which 1325 individuals from a well-defined Colombian population were involved. TIRAP (MAL) S180L genotyping was done by using a polymerase chain reaction-restriction fragment length polymorphism technique and by direct sequencing. Results: Leu180 allele was found to be a protective factor against developing TB (odd ratio (OR): 0.53, 95% confidence interval (CI): 0.29-0.97) and SLE (OR: 0.29, 95% CI: 0.14-0.61) while no significant influence on RA, pSS and T1D was observed. Conclusion: These results support the influence of TIRAP (MAL) S180L polymorphism on TB and indicate that TB and SLE might share a common immunogenetic pathway in the innate immune response. © 2008 Elsevier B.V. All rights reserved.